Increased expression of desmin and vimentin reduces bladder smooth muscle contractility via JNK2. Issue 2 (16th December 2019) - Javed, Elham; Thangavel, Chellappagounder; Frara, Nagat; Singh, Jagmohan; Mohanty, Ipsita; Hypolite, Joseph; Birbe, Ruth; Braverman, Alan S.; Den, Robert B.; Rattan, Satish; Zderic, Stephen A.; Deshpande, Deepak A.; et al.
Abstract: Bladder dysfunction is associated with the overexpression of the intermediate filament (IF) proteins desmin and vimentin in obstructed bladder smooth muscle (BSM). However, the mechanisms by which these proteins contribute to BSM dysfunction are not known. Previous studies have shown that desmin and vimentin directly participate in signal transduction. In this study, we hypothesized that BSM dysfunction associated with overexpression of desmin or vimentin is mediated via c‐Jun N‐terminal kinase (JNK). We employed a model of murine BSM tissue in which increased expression of desmin or vimentin was induced by adenoviral transduction to examine the sufficiency of increased IF protein expression to reduce BSM contraction. Murine BSM strips overexpressing desmin or vimentin generated less force in response to KCl and carbachol relative to the levels in control murine BSM strips, an effect associated with increased JNK2 phosphorylation and reduced myosin light chain (MLC20 ) phosphorylation. Furthermore, desmin and vimentin overexpressions did not alter BSM contractility and MLC20 phosphorylation in strips isolated from JNK2 knockout mice. Pharmacological JNK2 inhibition produced results qualitatively similar to those caused by JNK2 knockout. These findings suggest that inhibition of JNK2 may improve diminished BSM contractility associated with obstructive bladder disease.